Medial Epicondylitis: Evaluation and Management. Issue 6 (June 2015) - Amin, Nirav H.; Kumar, Neil S.; Schickendantz, Mark S.
Abstract : Medial epicondylitis, often referred to as "golfer's elbow, " is a common pathology. Flexor-pronator tendon degeneration occurs with repetitive forced wrist extension and forearm supination during activities involving wrist flexion and forearm pronation. A staged process of pathologic change in the tendon can result in structural breakdown and irreparable fibrosis or calcification. Patients typically report persistent medial-sided elbow pain that is exacerbated by daily activities. Athletes may be particularly symptomatic during the late cocking or early acceleration phases of the throwing motion. Nonsurgical supportive care includes activity modification, NSAIDs, and corticosteroid injections. Once the acute symptomology is alleviated, focus is turned to flexor-pronator mass rehabilitation and injury prevention. Surgical treatment via open techniques is typically reserved for patients with persistent symptoms.